Comparing labor supply elasticities in Europe and the US: New results - Olivier Bargain; Kristian Orsini; Andreas Peichl (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
We suggest the first large-scale international comparison of labor supply elasticities for 17 European countries and the US, separately by gender and marital status. Measurement differences are netted out by using a harmonized empirical approach and comparable data sources. We find that own-wage elasticities are relatively small and much more uniform across countries than previously thought. Differences exist nonetheless and are found not to arise from different tax-benefit systems or demographic compositions across countries. Thus, we cannot reject that countries have genuinely different preferences. Three other results, important for welfare analysis, are consistent over all countries: the extensive (participation) margin dominates the intensive (hours) margin; for singles, this leads to larger labor supply responses in low-income groups; income elasticities are extremely small everywhere. Finally, the results for cross-wage elasticities in couples are opposed between regions, consistent with complementarity in spouses' leisure in the US versus substitution in spouses' household production in Europe.
Keywords: C25; C52; H31; J22; 330; household labor supply; elasticity; taxation; Europe; US